Uji Kinerja Sistem Fertigasi Tanaman Bawang Merah (Allium cepa L.) - Wahyuni, Leni Tri; Tusi, Ahmad; Amien, Elhamida Rezkia (abe.fp.unila.ac.id, 2023)
The purpose of the fertigation system is to meet the needs for irrigation and fertilizer for plants provided simultaneously through the drip irrigation system. Appropriate application of fertilizer and irrigation (both quantity and time of application) is the key to the growing process of shallot plants. The aim of the research was to test the fertigation system, analyze the performance of the fertilizer injector, and determine the uniformity of the drops in the drip fertigation system. Fertigation with a drip irrigation system design using a dripper line emitter (Streamline X, 16 mm diameter) with a spacing of 30 cm, 1-2inch PVC type manifold pipes, 4inch main pipe PE type, and 2 - 3inch PE type sub-main pipe. The water distribution method used a pump with a discharge of 13 m³/hour, a fertilizer injector with an injector (dosing proportional mix-rite), and an automatic control box system using NMC Pro. The variables observed were coefficient of uniformity (CU), fertilizer injector performance, and wetting diameter on the soil surface. The results showed that the appropriate fertilizer injector size setting for plant growth in each shallot growth phase was 0.3, 0.4, and 0.5. The irrigation efficiency and CU value were 96 % and 86 % respectively, which means that the water distribution via dripper lines has good uniformity with an average wetting diameter of 22 cm. Keywords: Coefficient of Uniformity, Dripper Lines, Fertigation, Fertilizer Injectors, Shallots.